Qualitative Methodology in Cardiovascular Outcomes Research: A Contemporary Look. Issue 9 (September 2019) - McIlvennan, Colleen K.; Morris, Megan A.; Guetterman, Timothy C.; Matlock, Daniel D.; Curry, Leslie
Abstract : Qualitative research offers unique opportunities to contribute to cardiovascular outcomes research. Despite the growth in qualitative research over the last decade, outcomes investigators in cardiology still have relatively little guidance on when and how best to implement these methods in their investigations, leaving the full potential of these methods unrealized. We offer a contemporary look at qualitative methods, including publication trends of qualitative studies in cardiology journals from 1998 to 2018, novel emerging data collection and analytic methods, and current use and examples of cardiovascular outcomes research that apply qualitative methods such as user-centered design, preimplementation evaluation, implementation evaluation, effectiveness evaluation, and policy analysis.